Postmastectomy intensity modulation radiated therapy of chest wall and regional nodes: Retrospective analysis of the performance and complications up for 5 years. Issue 39 (September 2017) - Wang, Qiong; Jie, Wuyun; Liang, Zhiwen; Wu, Hongge; Cheng, Jing
Abstract : Abstract: To retrospectively evaluate the performance and complications of postmastectomy intensity modulation radiated therapy (IMRT) technique. From January 2010 to December 2014, IMRT technique was applied to 200 patients after modified radical mastectomy. The acute and late radiation toxicities have been followed up for 5 years. The treatment performance, toxicity incidence, and risk factors were investigated. All patients included had at least 1-year of follow-up; mean follow-up was 28.5 months. Three patients had grade 3 acute radiation dermatitis; 1 patient received grade 2 acute radiation induced lung injury, while 3 patients received acute radiation esophagitis. Seven patients had edema at the end of radiotherapy. Multivariate analyses revealed that neoadjuvant chemotherapy and hypertension were the most significant risk factors for acute skin dermatitis and acute radiation induced lung injury, respectively. Trastuzumab treatment was the independent risk factor for late radiation lung injury. Internal mammary nodes irradiation might relate to acute and late radiation induced lung injury. In the follow-ups there were 125 patients that were followed up with for >2 years. The 2-year local-regional recurrence (LRR), distant metastasis (DM), and disease free survival (DFS) were 1.6%, 6.4%, and 92.80%, respectively. Postmastectomy treatment with the IMRT technique can reduce the incidence rate of radiation toxicity by decreasing organs at risk (OARs) irradiation. Patients with risk factors for radiation toxicity should be strictly surveyed throughout radiotherapy.